Downfall of the current antibody correlates of influenza vaccine response in yearly vaccinated subjects: Toward qualitative rather than quantitative assays. Issue 1 (20th October 2015) - Cagigi, Alberto; Cotugno, Nicola; Rinaldi, Stefano; Santilli, Veronica; Rossi, Paolo; Palma, Paolo
Abstract: Response to seasonal influenza vaccination is currently evaluated by antibody correlates that estimate vaccine seroconversion as well as immune protection. These correlates rely on the general dogmas surrounding seasonal influenza vaccination; that is, that vaccine‐induced antibodies would exclusively generate immunity to influenza vaccine strains and that protective immunity would wane before the next season. Here, we summarize recently reported data on immunity to seasonal influenza in healthy individuals and rediscuss results on yearly vaccinated pediatric immunocompromised patients that together highlight the need for revision of the current correlates of vaccine response to shift from quantitative to qualitative measurements.